Web-based information systems in Iran - Mohammad Hosseini Ronaghi (مطالعات مدیریت کسب و کار هوشمند, 2012)
The current global situation is characterized by the interrelated, complex uncertainty, volatile and dynamic business environments. This has encouraged the appearance of critical risks that can impact on the firms’ performance. This article aims to uncover some important dimensions of the organizational change issues around ERPII projects. The results indicate that the lack of suitable data centers, telecommunication infrastructure problems and costs of software will impact on implementation of integrated web-based information systems in Iran